Peran Hormon Kortikosteroid dalam Regulasi Metabolisme dan Respons Stres pada Manusia - Devina Adira Azzahra; Septi Puspita Kurniawati; Juwita Ramadhani Octavianingrum; Liss Dyah Dewi Arini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Corticosteroid hormones play a vital role in maintaining human homeostasis by regulating energy metabolism and stress responses. Glucocorticoids, such as cortisol, and mineralocorticoids, such as aldosterone, have specific functions in metabolic processes and electrolyte balance. Activation of the hypothalamic-pituitary-adrenal (HPA) axis during stress responses triggers corticosteroid release, enabling the body to cope with physical and psychological challenges. However, corticosteroid dysregulation can lead to various clinical disorders, such as Cushing's syndrome and Addison's disease, impacting metabolism and overall health. Furthermore, while corticosteroids are widely used in treating inflammatory and autoimmune diseases, prolonged use can cause severe side effects. This article aims to review the mechanisms, physiological roles, pathological impacts, and therapeutic potentials of corticosteroid hormones. The findings highlight the importance of managing these hormones in clinical conditions and the opportunities for developing more targeted and safer therapies.